2017
DOI: 10.1038/s41598-017-03102-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepatitis B core antibody as a biomarker of hepatic inflammation in chronic hepatitis B patients with normal alanine aminotransferase

Abstract: Our previous studies unexpectedly indicated that the level of serum hepatitis B core antibody (anti-HBc) was positively correlated with the serum alanine aminotransferase (ALT) level. The aim of this study was to determine whether anti-HBc could serve as a potential biomarker for the detection of liver inflammation in chronic hepatitis B (CHB) patients, especially in patients with normal ALT levels. Serum anti-HBc levels were quantified in 655 treatment-naïve CHB patients, including 45 patients who underwent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 30 publications
4
67
0
2
Order By: Relevance
“…Anti‐HBc showed a high diagnostic accuracy for identifying moderate or severe inflammation in all patients and in patients with ALT below 64 IU/L (AUROC = 0.768 and 0.767, respectively) in a study including 469 treatment‐naïve CHB patients . Anti‐HBc showed an AUROC of 0.87 and 0.75 for identifying moderate or severe inflammation in HBeAg (+) and HBeAg (−) patients, respectively, in another study that included 193 treatment‐naïve CHB patients with normal ALT . However, the possible mechanism underlying the roles of anti‐HBc in hepatic inflammation throughout chronic HBV infection is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti‐HBc showed a high diagnostic accuracy for identifying moderate or severe inflammation in all patients and in patients with ALT below 64 IU/L (AUROC = 0.768 and 0.767, respectively) in a study including 469 treatment‐naïve CHB patients . Anti‐HBc showed an AUROC of 0.87 and 0.75 for identifying moderate or severe inflammation in HBeAg (+) and HBeAg (−) patients, respectively, in another study that included 193 treatment‐naïve CHB patients with normal ALT . However, the possible mechanism underlying the roles of anti‐HBc in hepatic inflammation throughout chronic HBV infection is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the development of noninvasive approaches for predicting liver inflammation or fibrosis based on LSM and serum markers, either alone or in combination, such as AST‐to‐ALT ratio (AAR) and aspartate aminotransferase‐to‐platelet ratio index (APRI), decreases the need of liver biopsy . However, all approaches are used to detect inflammation or fibrosis separately, rather than simultaneously . Furthermore, only a few articles have evaluated the performance of noninvasive models and there is no approach that is associated with antiviral therapy decision‐making in CHB patients with ALT < 2ULN …”
Section: Introductionmentioning
confidence: 99%
“…Bertoletti et al challenged the concept of an immune‐tolerant phase . Zhou et al reported that anti‐HBc is a biomarker of hepatic inflammation in adults with CHB and a normal ALT level . Together, these findings suggest that some CHB patients considered to be in the immune‐tolerant phase were actually experiencing active inflammation and mounting anti‐HBV immune response.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that anti‐HBc level is predictive of spontaneous HBeAg seroconversion. Anti‐HBc has potential as a marker for making AVT decisions in CHB patients with a normal ALT level . All of our patients were initially in the HBeAg‐positive normal ALT phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation